First complete genome sequence and molecular characterization of Canine morbillivirus isolated in Central Brazil - Vivaldo Gomes da Costa (Nature Portfolio, 2021)
Abstract The Brazilian regions are still highly endemic areas for Canine morbillivirus [canine distemper virus (CDV)]. However, little is known regarding the genetic variability of the strain circulating in several Brazilian regions. Here, we report the first full-length genome and molecular characterization of CDV isolated from domestic dogs in the Brazilian Center-West region. Sequence alignment and phylogenetic analyses based on deduced amino acid and nucleotide sequences showed that the isolated strain is characterized as the South America-I/Europe genotype. However, it segregates into a CDV subgenotype branch. Interestingly, both H and F proteins have a gain of a potential N-glycosylation sites compared to the Onderstepoort vaccine strain. Therefore, this study provides a reference to further understand the epidemic and molecular characteristics of the CDV in Brazil.